Evaluation of cellulose triacetate hollow fiber membrane for volume reduction of real industrial effluents through an osmotic concentration process: A pilot-scale study - Abdelrahman M. Awad (16932519) (2021)
The current article tackles the challenge of reducing wastewater volumes generated from the gas industry. A forward osmosis (FO) pilot unit, deployed as osmotic concentration (OC) process without the draw solution (DS) recovery step, was applied as an option for volume reduction of real industrial effluents. A commercial hollow fiber (HF) FO membrane fabricated from Cellulose Triacetate (CTA) was firstly tested with synthetic feed solution (FS) to investigate the separation properties of the membrane and to identify the optimum operating conditions of the pilot unit. The pilot plant was then challenged with real industrial wastewater for an extended period of operation, primarily to assess membrane-fouling propensities and other performance parameters. Results revealed that according to the operating conditions, the CTA membrane can achieve feed recoveries between 60%–90%, at water fluxes between 2.24-1.65 L.m−2 h−1 (LMH)). The operation at 75% feed recovery was identified as the optimum condition since it showed the lowest specific solute flux (20.93 mmol L−1) at a water flux of 1.94 LMH. Outcomes of pilot testing with the real wastewater demonstrated operational stability for over 50 h of continuous operation. The pilot system recovered 75% of the wastewater feed at a stable flux trend with minimal flux decline. Water flux of 1.76 LMH was recorded along with reverse solute flux of 292 mmol h−1. The water flux was observed to decline slightly by only 5.6%, which was attributed to inorganic scaling on the membrane surface where cleaning with citric acid solution demonstrated efficacy in restoring the initial flux. Other Information Published in: Environmental Technology & Innovation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eti.2021.101873